2021
DOI: 10.1186/s12938-021-00897-1
|View full text |Cite
|
Sign up to set email alerts
|

COMSOL Multiphysics® modelling of oxygen diffusion through a cellulose nanofibril conduit employed for peripheral nerve repair

Abstract: Background Peripheral nerve injury can cause significant impairment, and the current methods for facilitating repair, particularly over distances greater than approximately 1 mm, are not entirely effective. Allografts, autografts, and synthetic conduits are three of the most common surgical interventions for peripheral nerve repair; however, each has limitations including poor biocompatibility, adverse immune responses, and the need for successive surgeries. A potential new method for promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although Hernández-Cortés et al did not show an effect in preventing perineural adhesions using a cellulose-based wrapping material [25], cellulose has been examined with positive results in other research, including use around nerves and tendons to prevent adhesions [63][64][65]. Improved oxygen and glucose diffusion through cellulose conduits to nerves has been demonstrated [66,67]. Supporting the promising literature, Yamamoto et al showed perineural adhesion prevention after using a CMC-PE gel [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although Hernández-Cortés et al did not show an effect in preventing perineural adhesions using a cellulose-based wrapping material [25], cellulose has been examined with positive results in other research, including use around nerves and tendons to prevent adhesions [63][64][65]. Improved oxygen and glucose diffusion through cellulose conduits to nerves has been demonstrated [66,67]. Supporting the promising literature, Yamamoto et al showed perineural adhesion prevention after using a CMC-PE gel [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another tier of modeling (using COMSOL Multiphysics) focused on diffusion with variables other than fluid convection. Some setups include diffusion in porous media with temperature-induced variation in diffusivity [11], diffusion with a chemical reaction [12], diffusion in a porous media in an electric field [13], diffusion of solute amongst two fluids with one displacing the other [14], and diffusion in a liquid in a tube replicating nerve fibers containing semipermeable membranes for walls [15]. Furthermore, simulations of brain characteristics have been demonstrated with a probe compressing brain tissue [16], changes in chemical reactions with motion induced by probes [17], and a brain model with tumor growth represented as an advancing concentration profile of tumoral cellular spread [18].…”
Section: Clinical Backgroundmentioning
confidence: 99%